Generalized actinobacillosis in a cow - Enver Beytut; Mehmet Tuzcu (Eurasian Journal of Veterinary Sciences)
In the present case, generalized actinobacillosis in a cow was described. Diffuse granulomas varying in size from ptn head to chickpea were seen on the peritoneum, liver, uterus and diaphragm. Microscopical examination revealed that the granulomas were characterized by colonies of bacteria surrounded by radially arranged projections in the center of neutrophil leucocyles which were again surrounded by macrophages and giant cells of Langhans type with outer fibrous capsule including lymphocyte and plasma cells. The sections stained with Brown and Brenn, Ziehl-Neelsen and Gridley methods were positive for Gram-negative bacteria; negative for acid-fast bacilli and mycotic agents, respectively.